The attack of the present on the remainder of time: some remarks on historiography from nineteenth-century India - Frese, Heiko (South Asia, 2012)
Using the example of a local chronicle from early nineteenth-century Orissa, this article discusses the structure, content and strategy of selected historiographical texts of the period. Contemporary events and the immediate past can be identified in the texts and indeed govern their plots, reflecting a new representation of reality in historiography of this kind. Thus, the changing hegemonic order of such texts—where content begins to override form—mirrored the changing political world. Colonial discourse started to soak into Indian historiography.